Sistem Informasi Nilai Siswa pada SMP Karya Bhakti Berbasis Web - Limbong, Tonni; Tarigan, Aldi T (UNIKA Santo Thomas, 2022)
The information system for processing student grade data at Karya Bhakti Middle School is currently not fully computerized. In processing student grade data, currently it is still done manually, such as using the Microsoft Excel module which has been designed and then given to the subject teacher and homeroom teacher during the process of filling in grades. This is one of the weaknesses where in the improvement of today's technology, a system with processes involving big data should be done easily and online. In this study the authors design and build a system that is expected to overcome these various problems. Data mining methods used are interviews, observation, and literature studies